1983
DOI: 10.1007/bf00343429
|View full text |Cite
|
Sign up to set email alerts
|

Parental rearing behaviour and personality characteristics of depressed patients

Abstract: Within the framework of a large and ongoing study of depression in its biological, clinical, psychological and social aspects, 141 patients of both sexes in the age range 21 to 65 years participated in a study of parental rearing practices and personality characteristics. The perceived parental rearing behaviour was assessed by means of a specially constructed inventory (EMBU), and the personality characteristics by means of a Swedish personality inventory, the KSP, which had previously been shown to measure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
1
9
0
4
Order By: Relevance
“…Parenting styles are important in understanding mental health of children and parents as well as the development of personality (e.g., Benhaminsen et al 1984;Bowlby 1940;Fukunishi et al 1992;George and Main 1979;Kendler et al 1997;Koestner et al 1991;McCrae and Costa 1988;Mussen et al 1970;Nakao et al 2000;Parker 1993;Perris et al 1983;Richter et al 2000) and the onset of psychopathology (e.g., Alnas and Torgensen 1990;Eriksson et al 1986;Heider et al 2006;Lieb et al 2000;Parder 1981;Russell et al 1992;Torgersen 1985). Parenting styles may be transmitted intergenerationally.…”
Section: Introductionmentioning
confidence: 99%
“…Parenting styles are important in understanding mental health of children and parents as well as the development of personality (e.g., Benhaminsen et al 1984;Bowlby 1940;Fukunishi et al 1992;George and Main 1979;Kendler et al 1997;Koestner et al 1991;McCrae and Costa 1988;Mussen et al 1970;Nakao et al 2000;Parker 1993;Perris et al 1983;Richter et al 2000) and the onset of psychopathology (e.g., Alnas and Torgensen 1990;Eriksson et al 1986;Heider et al 2006;Lieb et al 2000;Parder 1981;Russell et al 1992;Torgersen 1985). Parenting styles may be transmitted intergenerationally.…”
Section: Introductionmentioning
confidence: 99%
“…Parenting styles (warmth and control) have been viewed as very important in understanding the mental health of children and parents as well as childhood personality development [1][2][3][4][5][6][7][8][9][10][11][12] and the onset of mental illnesses in adulthood [13][14][15][16][17][18][19]. Parents' rearing behaviours are similar to those experienced by their own parents when they were children.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study aimed at investigating possible connections between the experience of parental rearing practices and the person ality characteristics in the same series of pa tients [Perris et al, 1983b] we showed that significant positive and negative relation ships occur between different orientations in parental rearing practice (e.g. affectionate versus rejecting or depriving) and various personality traits, in particular those referring to the variables which distinguish the patient groups from the controls.…”
Section: Comments and Conclusionmentioning
confidence: 99%